The Role of Social Media in Increasing Social Interaction in Language Learning in Indonesian Higher Education - Luana Sasabone; Sugeng Irianto; Indra Tjahyadi; Dahlan Abdullah (Yayasan Adra Karima Hubbi, 2023)
Background. Student inactivity in social interaction is a serious problem in Indonesian higher education, it can affect the quality of language learning. The learning structure tends to be one-way from lecturer to student, creating a dynamic like an inverted pyramid, with limited social interaction. Therefore, this research aims to explore the role of social media in enriching social interactions and improving language learning in higher education environments. Purpose. The purpose of this research is to investigate and understand in depth the role of social media in increasing students' social interactions during the language learning process in Indonesian higher education. By achieving this goal, this research seeks to provide practical recommendations for increasing the effectiveness of language learning and creating a foundation for the development of more adaptive social media-based learning strategies. Method. This research uses a quantitative approach with survey methods. The questionnaire was designed using Google Form and distributed to 30 students who were studying Arabic and English at various universities in Indonesia. The data analysis technique adopts the Miles Huberman technique with a focus on students' understanding of the contribution of social media to increasing social interaction in language learning. Results. The research results show that students actively use social media such as Facebook, Twitter, Instagram, and WhatsApp to discuss, share learning resources, and collaborate on learning projects. Evaluation of the integration of social media in learning materials shows that the majority of students think that lecturers have integrated social media well. Conclusion.` This research provides a comprehensive picture of the positive impact of social media in language learning in higher education. By involving increased interaction, collaboration, and understanding of language material, this research creates a foundation for the development of learning strategies that are more focused on social media integration.